Lymphovascular invasion is a dominant risk factor for lymph node metastasis in T2 rectal cancer - Medic, Selma; Nilsson, Emelie; Rönnow, Carl-Fredrik; Thorlacius, Henrik (Endoscopy International Open, 2024)
Background and study aims Surgical resection is standard treatment of T2 rectal cancer due to risk of concomitant lymph node metastases (LNM). Local resection could potentially be an alternative to surgical treatment in a subgroup of patients with low risk of LNM. The aim of this study was to identify clinical and histopathological risk factors of LNM in T2 rectal cancer.Patients and methods This was a retrospective registry-based population study on prospectively collected data on all patients with T2 rectal cancer undergoing surgical resection in Sweden between 2009 and 2021. Potential risk factors of LNM, including age, gender, resection margin, lymphovascular invasion (LVI), histologic grade, mucinous cancer, and perineural invasion (PNI) were analyzed using univariate and multivariate logistic regression.Results Of 1607 patients, 343 (21%) with T2 rectal cancer had LNM. LVI (odds ratio [OR] = 4.21, P < 0.001) and age < 60 years (OR = 1.80, P < 0.001) were significant and independent risk factors. However, PNI (OR = 1.50, P = 0.15), mucinous cancer (OR = 1.14, P = 0.60), histologic grade (OR = 1.47, P = 0.07) and non-radical resection margin (OR = 1.64, P = 0.38) were not significant risk factors for LNM in multivariate analyses. The incidence of LNM was 15% in the absence of any risk factor.Conclusions This was a large study on LNM in T2 rectal cancer which showed that LVI is the dominant risk factor. Moreover, low age constituted an independent risk factor, whereas gender, resection margin, PNI, histologic grade, and mucinous cancer were not independent risk factors of LNM. Thus, these findings may provide a useful basis for management of patients after local resection of early rectal cancer.
Keywords: Endoscopy Lower GI Tract; Colorectal cancer; Polyps / adenomas / ...; Endoscopic resection (polypectomy, ESD, EMRc, ...); CRC screening